2020
DOI: 10.1177/0030222819900441
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effect of Group Flower Arranging Sessions on Caregiver Self-Efficacy and Stress Levels in an In-Patient Hospice

Abstract: This study was designed to promote enhanced self-efficacy and decreased stress levels for family caregivers at a hospice care hospital, thus increasing their quality of life. This is achieved through group flower arranging sessions. The objectives are to (a) enhance self-efficacy scores for family caregivers of Calvary patients, (b) decrease stress levels for family caregivers of Calvary patients, and (c) disseminate results to other hospices. The results show that the flower arranging sessions resulted in sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Our review of the literature identified that the research on natural environment therapies was largely concentrated on patient populations rather than informal cancer caregivers. In studies that involved cancer caregivers, one study focused on caregivers of patients at end-of-life [33], two were primarily focused on pediatric patients and their parent caregiver [34,35], one Table 1 illustrates the grid used to chart the data and summarize findings. Our review of the literature identified that the research on natural environment therapies was largely concentrated on patient populations rather than informal cancer caregivers.…”
Section: Stage 4 and 5: Charting The Data And Collating Summarizing And Reporting The Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our review of the literature identified that the research on natural environment therapies was largely concentrated on patient populations rather than informal cancer caregivers. In studies that involved cancer caregivers, one study focused on caregivers of patients at end-of-life [33], two were primarily focused on pediatric patients and their parent caregiver [34,35], one Table 1 illustrates the grid used to chart the data and summarize findings. Our review of the literature identified that the research on natural environment therapies was largely concentrated on patient populations rather than informal cancer caregivers.…”
Section: Stage 4 and 5: Charting The Data And Collating Summarizing And Reporting The Resultsmentioning
confidence: 99%
“…Our review of the literature identified that the research on natural environment therapies was largely concentrated on patient populations rather than informal cancer caregivers. In studies that involved cancer caregivers, one study focused on caregivers of patients at end-of-life [33], two were primarily focused on pediatric patients and their parent caregiver [34,35], one looked at a nature intervention along with other types of complementary therapies [36], and one study involved a physical activity intervention that could include activities in the natural environment [37]. Included sample sizes ranged from 34-106 caregivers who were aged 26-76 years, primarily female, and represented mixed race/ethnicities [33][34][35][36][37].…”
Section: Stage 4 and 5: Charting The Data And Collating Summarizing And Reporting The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The symbolic function that music plays can in a way be compared with that of flowers. In hospices, members of a patient’s family or other caregivers sometimes engage in arranging flowers, and this has been found to relieve stress and other associated experiences during mourning (Lavin et al., 2020).…”
Section: Discussionmentioning
confidence: 99%